Effects of Sangyod Rice as a Substitute for Wheat Flour on the Physical Properties of Butter Cake Products - Yampuang, Racharat; Poolcharoensil, Noppamas; Subanmanee, Natthaporn; Klangwijit, Sasiruk; Norajit, Krittika; Srabua, Phatraya; Thawerattanon, Nuttanun (Journal of Food Health and Bioenvironmental Science, 2023)
Sangyod is a native rice of Thailand and is used in many types of food owing to its high nutrient value. Indeed, it is used in bakery products to increase their nutritional value. In this study the effect of using Sangyod rice flour as a substitute for wheat flour in butter cakes was assessed. The physical properties of the butter cakes were produced using Sangyod rice flour 50%, 75% and 100% (by wheat flour weight). Increasing the amount of Sangyod rice flour resulted in a higher density batter and cake but lower specific volume. Scanning electron microscopy revealed that the microstructure of the butter cakes contained fewer air bubbles when the amount of Sangyod rice flour was increased, due to Sangyod rice not containing gluten, which traps air bubbles. Regarding the texture profile, the hardness and chewiness of the butter cakes were significantly higher when they were made with Sangyod rice rather than the control recipe (p ≤ 0.05). Furthermore, when the amount of Sangyod rice flour in the butter cakes was increased, the L* and b* values decreased and the a* value increased significantly (p ≤ 0.05).